Ionic liquid-enhanced soft resistive switching devices. Issue 96 (3rd October 2016) - Rajan, Krishna; Chiappone, Annalisa; Perrone, Denis; Bocchini, Sergio; Roppolo, Ignazio; Bejtka, Katarzyna; Castellino, Micaela; Pirri, Candido Fabrizio; Ricciardi, Carlo; Chiolerio, Alessandro
Abstract : Left: SEM showing dendrites bridging the electrodes. Right: Retention test showing a final on/off ratio of 700 after 10 000+ s. The addition of IL to switching matrix triggers non-volatile memory and 10-fold reduction of operating voltage. Abstract : Resistive switching phenomena are of paramount importance in the area of memory devices. In the present study, we have fabricated a simple resistive switching device using a solution processable nanocomposite based on silver nitrate and poly(vinylidene fluoride-hexafluoropropylene). The change in resistance is ascribed to an initial ionic conduction, followed by a non-continuous field induced filament formation. The switching device fabricated with the above-mentioned active matrix displayed a volatile switching behavior. The addition of room temperature ionic liquid plays a fundamental role in triggering permanent memory and reducing the set voltage range up to ten-fold. The change in switching behavior with respect to the applied voltage bias and compliance level set during electrical characterization was studied thoroughly. The present work also gives a glimpse into the importance of device architecture on resistive switching phenomena.